Partisanship, politics, and the energy transition in the United States: A critical review and conceptual framework. (July 2019) - Mayer, Adam
Abstract: Partisan rancor has markedly increased in the U.S., with significant divides between Republicans and Democrats in both the public and in government on a range of policy issues. Current partisanship extends beyond policy differences, however, in that Republicans and Democrats also hold different understandings of several empirical issues—such as climate change or the public health impacts of energy development. We propose a four-part conceptual framework to understand the role of partisanship in energy transition with a focus on the United States. We suggest that partisanship has four key dimensions: cue receptivity, expressive partisanship, negative partisanship, and performative partisanship. We identify research needs to understand and mitigate the role of partisanship in energy transition.